Studi interferensi mangan, krom, seng, tembaga dan nikel pada analisis kobalt secara spektrofotometri serapan atom tipe nyala - Nova Yuliasari; Yuniar Yuniar; Siti Nuraini; Hanida Yanti; Fahma Riyanti (Faculty of Mathtmatics and Natural Sciences, 2026)
Cobalt in the human health environment can be an essential mineral nutrient in nutritional intake or can also be the result of exposure to polluted environments. Applicable analytical methods such as flame-type atomic absorption spectrophotometry (AAS) are required in determining cobalt concentrations. Interference studies have been conducted due to information on potential interference with cobalt analysis using AAS. The study was conducted on simulated solutions containing manganese, chromium, zinc, copper, and nickel, each in a solution containing 2 mg/L cobalt. The statistical results of a completely randomized design (CRD) at a 95% confidence level or Î± 0.05 showed that the percentage of cobalt recovery in the presence of manganese, chromium, zinc, copper, and nickel up to 1,500 mg/L did not have a significant effect.The concentrations of manganese and chromium in formula milk samples, zinc in supplement samples, copper and nickel in shredded sea fish samples, and cobalt in these samples were at low concentrations, thus preventing interference with cobalt analysis in these samples.